Peningkatan Kompetesi Speaking Narrative dengan Menggunakan Model Pembelajaran Role Playing bagi Peserta Didik Kelas X 1 SMK Negeri 1 Toroh Kabupaten Grobogan pada Semester 2 tahun Pembelajara 2014/2015 - Lestari, Puspa (LP3 Universitas Negeri Semarang, 2016)
The outline of the research issue are how is the process of learning and improving speaking narative using the Role Playing model for students of class X-1 1st Toroh Senior Hight School 2nd Semester 2014/2015. The research is crried out though 2 cycles. Each cycle has two meetings. The subject of the research is the students of 1st Toroh Senior High School X-1 2nd semester school year 2014/2015. The average cycle I 80,26 with 66% reached the KKM and cycle OO average 85,39 with 89% reach the KKM, followed by a good atitude.